Assessing the Effectiveness of the UPLAND Program in Enhancing Farmers’ Income in Modoinding District - Gabryela Glory Sembel; Michael Mamentu; Johny Lengkong; Juan Gabriel Kaseger (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study analyzed the effectiveness of the UPLAND Assistance Program, implemented by the Department of Agriculture in the Minahasa Selatan Regency, in improving farmers’ incomes in Modoinding District. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation from selected informants. The results showed that the program partially achieved its objectives by improving access to agricultural inputs and infrastructure, though challenges remained in adaptation and coordination. The study implied that strengthening institutional collaboration and continuous technical support were essential for achieving sustainable agricultural development.